2003
DOI: 10.1359/jbmr.2003.18.8.1404
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor-1 (SDF-1) Recruits Osteoclast Precursors by Inducing Chemotaxis, Matrix Metalloproteinase-9 (MMP-9) Activity, and Collagen Transmigration

Abstract: Signals targeting OCs to bone and resorption sites are not well characterized. A chemoattractant receptor (CXCR4), highly expressed in murine OC precursors, mediated their chemokine (SDF-1)-induced chemoattraction, collagen transmigration, and MMP-9 expression. Thus, bone vascular and stromal SDF-1 may direct OC precursors into bone and marrow sites for development and bone resorption.Introduction: Although chemokines are essential for trafficking and homing of circulating hematopoietic cells under normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
196
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(210 citation statements)
references
References 78 publications
(193 reference statements)
13
196
0
1
Order By: Relevance
“…Gonzola et al showed that the SDF-l/CXCR4 axis is critical in mediating lung inflammation [ 151. Following attraction of precursors by the SDF-1/CXCR4 interaction, subsequent induction of matrix metalloproteinase-9 by SDF-1 was suggested to facilitate transmigration through the endothelial cell layer of blood vessels and homing in bones [30].…”
Section: Discussionmentioning
confidence: 99%
“…Gonzola et al showed that the SDF-l/CXCR4 axis is critical in mediating lung inflammation [ 151. Following attraction of precursors by the SDF-1/CXCR4 interaction, subsequent induction of matrix metalloproteinase-9 by SDF-1 was suggested to facilitate transmigration through the endothelial cell layer of blood vessels and homing in bones [30].…”
Section: Discussionmentioning
confidence: 99%
“…Its receptor is CXCR4 which expressed on hematopoeitic stem cells and lymphocytes, as well as malignant cells and osteoclast precursors (41)(42)(43). SDF-1 is expressed by bone marrow stromal cells and endothelial cells.…”
Section: Sdf-1 Alpha/cxcr-4mentioning
confidence: 99%
“…If this enzyme function is compromised, mineral dissolution does not occur (Kornak et al 2000). Matrix metallopeptidase-9 (MMP-9) appears to be essential for osteoclast migration and precursor recruitment into bone (Okada et al 1995;Yu et al 2003). Although MMP-9-knockout mice show defects in bone development, intraosseous angiogenesis and fracture repair rather than osteoclast bone resorption appear to be compromised in these animals (Colnot et al 2003).…”
Section: Introductionmentioning
confidence: 99%